Treatment outcome in alcoholism: a comparison of self-report and the biological markers carbohydrate-deficient transferrin and γ-glutamyl transferase - Mundle, Götz; Ackermann, Klaus; Günthner, Arthur; Munkes, Jörg; Mann, Karl (European addiction research, 1999)
The primary source for evaluating treatment outcome in alcoholism is usually verbal self-report. Because the validity of self-report is often doubted, more objective markers for treatment outcome are needed. In this study, we compared self-report data from 238 male alcohol-dependent patients participating in a combined 6-week inpatient followed by a 1-year outpatient treatment program with the biological markers carbohydrate-deficient transferrin (CDT) and γ-glutamyl transferase (GGT). According to self-report, over 70% of the patients had a positive treatment outcome (57% abstinence, 16% intermediate relapse). These results are supported by the general reduction of CDT and GGT during the treatment period (p < 0.001). When we performed a cross-sectional analysis at 6 months during the outpatient program, there was a high consistency of self-report data with the biological markers (CDT 93%, GGT 91%, CDT/GGT 85%). Our results support the hypothesis that in abstinence- oriented treatment programs, self-reports are valid and can be used as the basis of measurement for treatment outcome.